Photon Switching using Nonlinear PANDA Ring Resonetor - S. Songmuang; S. Punthawanunt; S. Mitatha; P.P. Yupapin (My University, 2011)
We propose a new system of an all optical switching system using an optical add/drop filter consisting of two nano ring resonators. The dynamic behavior of dark-bright soliton collision within the modified add/drop optical filter device, which it is known as PANDA ring resonator. By using the dark-bright soliton conversion control within the PANDA ring, the obtained output signals can be attenuated and used to perform the single photon switching, which is capable for security code application. Results obtained have shown that the random binary codes based on a single photon switching can be formed by using the polarized light components, dark and bright solitons, whereas the single photon switching codes can be obtained by using the attenuated dark-bright soliton conversion signals output signals.
Keywords: Optical burst switching; Advanced Fiber Laser Technologies